Human alpha-endosulfine, a possible regulator of sulfonylurea-sensitive KATP channel: molecular cloning, expression and biological properties. - Heron, L; Virsolvy, A; Peyrollier, K; Gribble, F; Le Cam, A; Ashcroft, F; Bataille, D (1998)
Sulfonylureas are a class of drugs commonly used in the management of non-insulin-dependent diabetes mellitus. Their therapeutic action results primarily from their ability to inhibit ATP-sensitive potassium (KATP) channels in the plasma membrane of pancreatic beta cells and thereby stimulate insulin release. A key question is whether an endogenous ligand for the KATP channel exists that is able to mimic the inhibitory effects of sulfonylureas. We describe here the cloning of the cDNA encoding human alpha-endosulfine, a 13-kDa peptide that is a putative candidate for such a role. alpha-Endosulfine is expressed in a wide range of tissues including muscle, brain, and endocrine tissues. The recombinant protein displaces binding of the sulfonylurea [3H]glibenclamide to beta cell membranes, inhibits cloned KATP channel currents, and stimulates insulin secretion. We propose that endosulfine is an endogenous regulator of the KATP channel, which has a key role in the control of insulin release and, more generally, couples cell metabolism to electrical activity.